The method of action in the case of spontaneous assemblies and riots - Tutun, Anamaria (Technium Social Sciences Journal, 2023)
In recent times, the number of protests has increased rapidly in Romania, what many participants in these movements do not know is that they are regulated by the law of public assemblies and any organization or participation in such a demonstration must strictly respect these laws and regulations . Law no. 60/1991 on the organization and conduct of public assemblies guarantees the freedom of citizens to express their political, social or other opinions, to organize rallies, demonstrations, demonstrations, processions and any other gatherings, as well as to participate in them, with the condition that the public assemblies in question are peaceful. Public gatherings that take place in markets, on public roads or in other open air places must be declared in advance to the relevant authorities and it is not allowed that they prevent the normal use of public roads, public transport, except for those authorized, the operation of public or private institutions, of education, culture and health or of economic units. Administrative institutions and local police bodies are obliged to ensure the smooth running of public gatherings, and the organizers are obliged to ensure all the necessary measures for the public gathering to take place without incident while respecting the provisions of the law. The organization of public gatherings is prohibited in immediate proximity to railway stations, ports, airports, metro stations, hospitals, objectives, economic units with installations, machinery orimachines with a high degree of danger in operation.